2012
DOI: 10.1111/j.1365-2141.2011.09017.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections and human cancers: the legacy of Denis Burkitt

Abstract: SummaryDenis Parsons Burkitt was born in 1911, and in the late 1950s, described the disease that has come to be known as Burkitt lymphoma based on cases he observed in Uganda. Subsequently, Burkitt lymphoma was recognized as the first human tumour associated with an infectious agent when Epstein–Barr virus was isolated from samples supplied by Burkitt. It is now recognized that over one‐quarter of cancers worldwide are tied to infections. Notably, liver cancer is linked to hepatitis B virus and hepatitis C vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…The polarization of these cells towards a pro-angiogenic, pro-tumor state appears to be enhanced by chronic viral infection and sustained inflammation. For example, the inflammatory state created by hepatitis B or C infection is estimated to account for 80% of hepatocellular carcinomas, and 70% of cervical cancers are attributed to human papilloma virus infection (17, 24). Chronic infection perpetuates the presence of T regulatory cells, which express high levels of pro-angiogenic VEGF (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polarization of these cells towards a pro-angiogenic, pro-tumor state appears to be enhanced by chronic viral infection and sustained inflammation. For example, the inflammatory state created by hepatitis B or C infection is estimated to account for 80% of hepatocellular carcinomas, and 70% of cervical cancers are attributed to human papilloma virus infection (17, 24). Chronic infection perpetuates the presence of T regulatory cells, which express high levels of pro-angiogenic VEGF (25).…”
Section: Discussionmentioning
confidence: 99%
“…Different from tumor cell-directed approaches, there is evidence that acute activation of the immune system by a pathogen results in a bystander effect on tumor growth (15, 16). Studies using mouse models have revealed that acute infection with Toxoplasma gondii , listeria monocytogenes , and the Armstrong strain of lymphocytic choriomeningitis virus (LCMVa) have anti-tumor effects, whereas chronic infections such as Hepatitis C promote tumor growth, making the relationship between an active immune response and tumor growth unclear (16, 17). There have been several attempts to use controlled infection as a means of treating cancer, but have been met with limited success.…”
Section: Introductionmentioning
confidence: 99%
“…Those early studies showed the value of combination therapy and CNS prophylaxis [5]. The uneven geographical patterns of BL, notably high incidence in low-lying humid areas in Africa suggested infectious etiology [6] and led to the discovery in 1964 of Epstein-Barr virus (EBV) [7] as the first human virus associated with a human cancer [8]. Today, EBV is designated as a Class 1 carcinogen for BL and is implicated in several other cancers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kenneth Simbiri, Instructor of Microbiology and Immunology at SUNY Upstate Medical University, presented a paper titled “Cancer in Africa in 21 st Century: Paradigm Shift”. He reviewed recent literature about associations between viruses and cancer and noted the unacceptably high burden of infection-associated cancers in Africa, including cervical, vulvar, conjunctival, and anal [8]. Given the overlap of high HIV rates in Africa with many virally associated cancers, he stressed the need for studies to be conducted about infectious agents causing cancer and utilizing that knowledge in cancer control efforts in Africa [37-39].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between infections and cancer: HPV (Human Papilloma Virus) infection and cervical cancer, Epstein Barr Virus (EBV) and Burkitt Lymphoma as well as Non-Hodgkin and Hodgkin Lymphoma, Hepatitis-C Virus and hepatocellular carcinoma, Kaposi Sarcoma Herpes Virus (KSHV) and Kaposi Sarcoma[8].…”
mentioning
confidence: 99%